شبكات التواصل الاجتماعية ودورها في الرفع من الصورة الذهنية للعلامات التجارية - دراسة حالة: موبيليس الجزائر - - بن يامين خالد (جامعة الوادي University of Eloued, 2024)
This study aims to identify the role that social media networks play in enhancing the brand image, with a focus on Mobilis as a case study. The research emphasizes the importance of the company's presence on social media platforms, examining the content it shares and how it manages this presence to reinforce and enhance the brand image among its customers.To verify this, an online questionnaire was distributed to a random sample of Mobilis customers across various social media platforms. The data collection and analysis were conducted using the SPSS statistical program. The findings indicate a statistically significant impact of social media platforms on the brand image of Mobilis, showing a positive correlation.
"Social Media Networks and Their Role in Enhancing the Brand Image: A Case Study of Mobilis Algeria"
Keywords: مواقع; تواصل الاجتماعي; صورة ذهنية; علامة تجارية; صفحة موبيليس